2019
DOI: 10.1038/s41563-019-0454-9
|View full text |Cite
|
Sign up to set email alerts
|

Spin chirality fluctuation in two-dimensional ferromagnets with perpendicular magnetic anisotropy

Abstract: Non-coplanar spin textures with scalar spin chirality can generate effective magnetic field that deflects the motion of charge carriers, resulting in topological Hall effect (THE), a powerful probe of the ground state and low-energy excitations of correlated systems 1-3 . However, spin chirality fluctuation in two-dimensional ferromagnets with perpendicular anisotropy has not been considered in prior studies. Herein, we report direct evidence of universal spin chirality fluctuation by probing the THE above the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 34 publications
10
94
2
Order By: Relevance
“…However, spins of realistic materials own a threedimensional (3D) degree of freedom, making them different from the ideal XY model, in which the spin is confined within the 2D easy plane. Such an extra degree of freedom gives hope to many nontrivial topological spin states, such as skyrmions, magnetic bubbles, and merons 5,[16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…However, spins of realistic materials own a threedimensional (3D) degree of freedom, making them different from the ideal XY model, in which the spin is confined within the 2D easy plane. Such an extra degree of freedom gives hope to many nontrivial topological spin states, such as skyrmions, magnetic bubbles, and merons 5,[16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…More importantly, the size of skyrmions induced by the interfacial Dzyaloshinskii-Moriya interaction can reach ten nanometers, which can satisfy the demand of nanoscale spintronic devices. Furthermore, Wang et al [33] recently discovered the topological Hall effect in the single-layer ferromagnetic ultra-thin films, SrRuO3 and V-doped Sb2Te3 (Fig. 6), and they suggested that the spin chiral might be a common feature of two-dimensional ultra-thin ferromagnetic materials with perpendicular magnetization.…”
Section: Skyrmions and Topological Hall Effectmentioning
confidence: 99%
“…From this perspective, the anomalous Hall effect should be absent in antiferromagnetic materials with zero net magnetization. [33] However, studies on the anomalous Hall effect in the recent two decades reveal that both the intrinsic mechanism Berry curvature and extrinsic mechanisms including skew scattering and side jump can yield anomalous Hall conductivity. As a result, in 2014, Chen et al [36] theoretically predicted that a surprisingly large anomalous Hall effect that is the same order of magnitude with ferromagnetic transition metals exists in the noncollinear antiferromagnetic material Mn3Ir.…”
Section: Anomalous Hall Effect and Weyl Fermions In Noncollinear Antimentioning
confidence: 99%
“…A wide range of perovskite oxide heterostructures provide a fertile playground for discovering emergent properties owing to their diverse capabilities to tune delicate coupling between spin, charge, and orbital degrees of freedom [1][2][3] . The two-dimensional electron/hole gas at LaAlO 3 /SrTiO 3 interface 4,5 , polar skyrmions in PbTiO 3 /SrTiO 3 superlattice 6 , chiral spin fluctuation in 2D SrRuO 3 ferromagnet, 7 and the newly discovered infinite layer nickelate superconductor 8 are just several remarkable examples out of many. Engineering the lattice structure through interfacial mismatch of lattice constant [9][10][11] and symmetry [12][13][14] is one key route toward desired electronic phases and functionalities.…”
Section: Introductionmentioning
confidence: 99%